Hubungan Pelaksanaan Program Usaha Kesehatan Sekolah Terhadap Perilaku Hidup Bersih Dan Sehat Pada Siswa SDN 13 Seberang Padang Utara: The Relationship Between the Implementation of the School Health Program and Clean and Healthy Living Behaviors Among Students at SDN 13 Seberang Padang Utara - Nadia; Rika Sabri; Yonrizal Nurdin (NERS Jurnal Keperawatan, 2012)
School-age children is a critical age group because they are vulnerable of health issues. Health issues more dominant in school-age children are clean and healthy behavior. To encourage formation of the behavior required support from School Health Program (UKS) that the implementation not only focused on promotive and preventive efforts but also curative and rehabilitative. Howerver, at this time the implementation of the program was not maximal in Indonesia. The purpose of the research was to analyze the relationship between the school health program and clean and healthy behavior of students at SDN 13 Seberang Padang Utara. The research was a descriptive analytic study with cross sectional design.. The research was conducted from April 28 to May 5, 2012 with 98 samples consist of 4th, 5th and 6th grade. The data was collected by using questionnaires and behavioral observation sheet. The result of data analysis by using a Chi-Square test showed that more than half of respondents have a clean and healthy behavior in medium category, most of respondents said the implementation of the school health program included in good category and there was a significant association between the implementation of the school health program with clean and healthy behaviors of students. Recommended to the schools and Seberang Padang health centers to be able to work together for the success of school health programs such as "little doctors" and BIAS.